A Study and Performance Evaluation of OpenDaylight Controller in Software Defined Networks (SDN) - دنده رضوان; العاتكي طلال; سينو رنيم (Latakia University Journal -Engineering Sciences Series, 2020)
Software defined networks SDN is one of the most influential types of networks in information and communication technology compared to all traditional network technologies where there are many challenges, SDN is one of the most promising solutions for the Internet in the future and provides a strong network infrastructure with high specifications and low cost, and represents the future of the next generation of network engineering due to the easy division of networks, programming, monitoring, control and management through a central control, and the separation of control plane from the data-forwarding plane in SDN networks facilitates the process of managing and developing networks, as this technology is currently used in data centers and wireless networks, and is a solution to many of the problems faced by traditional networks. SDN networks are characterized by sufficient dynamism to deal with the different conditions of the network, and the controller is one of its most important components and is considered the smartest component in the network, and given the importance of choosing the appropriate controller according to the different parameters and conditions of the SDN network,in this research we conducted an analysis of the characteristics of Software defined Networks, The analysis relied on comparing SDN networks with the presence of a single OpenDaylight controller (ODL) and the presence of several controllers ODL, OpenDaylight controller was chosen as one of the famous controllers and it is distinguished from others as an open source and contains a distributed datastore and is designed to suit the data center environment, Taking into account the OpenFlow protocol supported on the southern interface by this controller, the research includes simulations of software defined networks topologies using the Mininet emulator, and various scenarios and parameters such as data rate, packet delay, and throughput were analyzed by the D-ITG tool.